Aberrant regional homogeneity in multiple frequency bands in patients with alcohol use disorder - Ruan, Xia; Yu, Tingting; You, Cixing; Yang, Ming; Chen, Jun (Frontiers in Psychiatry, 2025)
BackgroundIt is unclear whether the alterations in neural oscillations in patients with alcohol use disorder (AUD) are specific to different frequency bands. We applied the regional homogeneity (ReHo) approach to examine intrinsic functional connectivity variations in various frequency bands in AUD patients.MethodsThirty-three AUD patients and 29 healthy controls (HCs) were enrolled in this study. The ReHo values in six frequency bands (conventional frequency band, 0.01–0.08 Hz; slow-2, 0.198–0.25 Hz; slow-3, 0.073–0.198 Hz; slow-4, 0.027–0.073 Hz; slow-5, 0.01–0.027 Hz; and slow-6, 0–0.01 Hz) were calculated and compared between the two groups. The performance of the ReHo on distinguishing AUD patients from HCs was examined using a receiver operating characteristic (ROC) curve. The correlation of functional changes in the network and alcohol dependence was evaluated.ResultsDecreased ReHo values were detected in two frequency bands, and the areas of decreased ReHo values were mainly located in the left inferior parietal lobule (IPL) and right middle frontal gyrus (MFG); the diagnostic efficiency of the ReHo differences in brain areas was respectively 0.876 and 0.868, with sensitivities of 90.0% and 76.7% and specificities of 70.0% and 86.7%. The clinical scale scores were not significantly correlated with the ReHo values in specific brain areas.ConclusionsOur findings demonstrate that the widespread abnormal brain activity in AUD patients is characterized by distinct patterns of neural oscillatory power across multiple frequency bands. This exploration may provide an objective imaging basis for understanding the pathophysiological mechanisms of AUD.